2012
DOI: 10.4236/mnsms.2012.22004
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Ferromagnetic Ordering Curie Temperature in N-Doped MgO under Hydrostatic Pressure

Abstract: We have explored the magnetic properties of Nitrogen doped cubic MgO using the full potential linearized augmented plane wave (FP-LAPW) method. The unit cell has 128 atoms, and two Nitrogen atoms are placed in the positions of oxygen sites. This corresponds to 3.125% doping concentration. Our calculations predict that the ferromagnetic state, with a magnetic moment of about 1.0 μB per Nitrogen-dopant, is more favorable in energy than the nonmagnetic state, and the ferromagnetic correlations are influenced by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Kuang et al also reported that these composite defects promote magnetism in the case of oxygen vacancies [84]. It is contemplated that local magnetic moment is induced by the composite defects around the oxygen vacancy, when the exchange splitting of the oxygen vacancy is enhanced either by the hybridization between the N-p and nearest neighbor O-p orbitals or by applying on-site Coulomb repulsion and exchange interaction [81][82][83].…”
Section: Oxygen Vacancy/composite Defects As a Source Of Magnetismmentioning
confidence: 99%
See 1 more Smart Citation
“…Kuang et al also reported that these composite defects promote magnetism in the case of oxygen vacancies [84]. It is contemplated that local magnetic moment is induced by the composite defects around the oxygen vacancy, when the exchange splitting of the oxygen vacancy is enhanced either by the hybridization between the N-p and nearest neighbor O-p orbitals or by applying on-site Coulomb repulsion and exchange interaction [81][82][83].…”
Section: Oxygen Vacancy/composite Defects As a Source Of Magnetismmentioning
confidence: 99%
“…Thus, the theoretical investigations were carried out in this direction to revive the role of oxygen vacancies [79][80][81][82][83].…”
Section: Oxygen Vacancy/composite Defects As a Source Of Magnetismmentioning
confidence: 99%